Contemporary public health : policy, planning, management - Gupta, J. P., Dr.; Sood, A. K., Prof.; Apothecaries Foundation (New Delhi, India) (New Delhi : Apothecaries Foundation ; Distributed by Sheriden Book Co., 2005)
With reference to India.
Includes bibliographical references and index.
Keywords: Public health -- India; Medical care -- India; Health planning -- India; Medical policy -- India; Birth control -- India